Fiber-based multifunctional nickel phosphide electrodes for flexible energy conversion and storage. Issue 24 (7th June 2016) - Zhang, Zheye; Liu, Shasha; Xiao, Jian; Wang, Shuai
Abstract : Fiber-based multifunctional nickel phosphide electrodes have been successfully prepared by facile electrodeposition of nickel nanoparticle arrays on a commercial carbon fiber followed by low-temperature phosphidation. With the synergistic effect from the hierarchically porous structure and chemical compositions, the resultant electrodes exhibit excellent performance for overall water-splitting electrocatalysis and flexible supercapacitors. Abstract : A fiber-based multifunctional nickel phosphide (NiP x ) electrode has been successfully prepared by facile electrodeposition of nickel nanoparticle arrays on a commercial carbon fiber (CF) followed by low-temperature phosphidation. As a result of the synergistic effect from the 3D porous structure, enhanced conductivity, and the two active components Ni 2+ and P δ − with rich valences, the resulting vertically aligned NiP x nanoflakes grown on the CF (CF@NiP x ) electrode exhibit superior bifunctional electrocatalytic hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) performance in an alkaline electrolyte as well as an ultrahigh specific volumetric capacitance of 817 F cm −3 at a current density of 2 mA cm −2 . For practical applications, an efficient CF@NiP x -based alkaline water electrolyzer, with strong durability, can achieve 10 mA cm −2 water-splitting current at a cell voltage of only 1.61 V ( iR uncorrected). Besides, a fiber-based flexible solid-state asymmetric supercapacitor device with CF@NiP x as the cathode and reduced graphene oxide attached on CF@Ni (CF@Ni@RGO) as the anode was observed to achieve a remarkable volumetric energy density of 8.97 mW h cm −3, excellent flexibility and superior long term cycling stability. All these results render our fiber-based CF@NiP x electrodes as an ideal platform for electrocatalysis and flexible electrochemical energy storage applications.